COVID 19 Strategic preparedness and response plan : monitoring and evaluation framework : 11 May 2021 (World Health Organization, 2021)
The COVID-19 Strategic Preparedness and Response Plan (SPRP) 2021 Monitoring and Evaluation Framework tracks global progress against the COVID-19 SPRP 2021 for the ten pillars of the public health response. The operational intelligence complements the epidemiologic information used to drive a global dynamic system of support and response. Monitoring SPRP 2021 implementation will support countries, partners and WHO in strategic thinking, operational tracking and course correction based on evidence and transparency to strengthen the response to COVID-19.
Keywords: Betacoronavirus; zdravotnické plánování; veřejné zdravotnictví; epidemický výskyt choroby; Health Planning; infekční lékařství; epidemiologické monitorování; Disease Outbreaks; COVID-19; Epidemiological Monitoring; epidemiologie